2007
DOI: 10.1115/1.2747259
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Combustion Induced Vortex Breakdown Driven Flame Flashback in a Premix Burner With Cylindrical Mixing Zone

Abstract: In earlier experimental studies of the authors a previously unknown mechanism leading to flame flashback—combustion induced vortex breakdown (CIVB)—was discovered in premixed swirl burners. It exhibits the sudden formation of a recirculation bubble in vortical flows, which propagates upstream into the mixing zone after the equivalence ratio has exceeded a critical value. This bubble then stabilizes the chemical reaction and causes overheat with subsequent damage to the combustion system. Although it was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 10 publications
0
36
0
1
Order By: Relevance
“…On the 13 other hand, heat and chemical species diffusion towards the wall tend to quench the flame [12][13][14]. It is argued 14 that flame flashback is the ultimate result of a competition between these two effects [5].…”
mentioning
confidence: 99%
“…On the 13 other hand, heat and chemical species diffusion towards the wall tend to quench the flame [12][13][14]. It is argued 14 that flame flashback is the ultimate result of a competition between these two effects [5].…”
mentioning
confidence: 99%
“…For the first time, these measurements were extended to confined swirling flows. Hence, theory validation for CIVB-driven flashback, developed by [71] on the basis of a numerical study, became feasible [72].…”
Section: Flashback In Premixed Swirl Flamesmentioning
confidence: 99%
“…Baroclinic push theory, firstly proposed by Ashurst [70], explained flame propagation in vortex tubes and could be used to explain the origin and onset of CIVB-driven flame propagation [71]. However, the fundamental mechanism of the flow transitions is not yet fully understood.…”
Section: Flashback In Premixed Swirl Flamesmentioning
confidence: 99%
“…Swirl stabilized premixed combustion is the dominant technology used to get control stabilized combustion in gas turbines and other combustion systems. Nevertheless, swirl burners with lean premixed combustion are prone to the following flashback mechanisms 1 , -Flame propagation in the wall boundary layer -Turbulent flame propagation in the core flow -Combustion instabilities, and -Combustion induced vortex breakdown (CIVB) Combustion induced vortex breakdown 2 has been identified as one source of sudden flame transition and flashback in swirl combustors where this sudden transition can cause severe system failure due to the risk of overheating of upstream burner positioned components.There have been considerable efforts and research focused on the understanding of this phenomenon [2][3][4][5][6][7][8] . However, there are still areas of improvement that need to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The group also used the vorticity transport equation 4 to analyse the source terms of the azimuthal components of the flow. They found that the CIVB is initiated by the baroclinic torque which produces considerable levels of negative axial velocity in the vortex core.…”
Section: Introductionmentioning
confidence: 99%